Preparation and Characterization of phenytoin Sodium-Controlled Release Solid Dosage Forms - Boontha, Supavadee; Saepang, Kamchai; Khondee, Supang; Pitaksuteepong, Tasana (Science Essence Journal, 2022)
This research aimed to prepare and characterize phenytoin sodium-controlled release solid dosage forms. Phenytoin sodium and hydroxypropyl methylcellulose (HPMC) were mixed at the ratio of 1:0 - 1:3 using physical mixing (PM) and solid dispersion (SD) methods. Compared with the Fourier transform infrared (FTIR) spectrum of phenytoin sodium and HPMC, the spectrum of the obtained mixture using the PM method demonstrated that there were no significant interactions between phenytoin and HPMC. However, the presence of interactions between phenytoin sodium and HPMC was detected when using the SD method. Disintegration time (DT) of all prepared capsules using various ratios of HPMC was less than 15 min. For the in vitro release of capsules, phenytoin released from phenytoin incorporated with HPMC was more than that from non-incorporated phenytoin. Phenytoin released from the formulated capsule with HPMC was increased with increasing of the amount of HPMC. Two pre-formulations (phenytoin sodium and HPMC= 1:2 and 1:3) were used to formulate tablets. Both tablet formulations met the requirement criteria for thickness, hardness, and weight variation (USP41). For the in vitro release of tablets, phenytoin released from the formulated tablet was lower than 5%. This was due to the formulated tablet remaining a viscous white gel in the dissolution basket at the end of the experiment. In conclusion, incorporating phenytoin with HPMC might be suitable for sustained phenytoin release in oral administered tablets. However, DT will be increased and the appropriate ratio of phenytoin sodium and HPMC will be investigated in further studies.